Combustion of primary and secondary pulp mill sludge and their respective blends with coal: A thermogravimetric assessment. (November 2015) - Coimbra, Ricardo N.; Paniagua, Sergio; Escapa, Carla; Calvo, Luis F.; Otero, Marta
Abstract: Properties of primary and secondary pulp mill sludge are unalike and are also very different from those of coal. Thermogravimetric analysis was used to assess the separate combustion of coal, primary and secondary pulp mill sludge. Then, the co-combustion of coal with primary and with secondary pulp mill sludge was studied under identical experimental conditions. Both Differential Thermogravimetry burning profiles (DTG) and Differential Scanning Calorimetric analysis (DSC) showed remarkable differences between the combustion of coal, primary and secondary paper mill sludge. However, compared with the combustion of coal, the effects of adding a 10 wt.% of either primary or secondary paper mill sludge were not relevant in terms of weight loss or heat release. This was further proved by non-isothermal kinetic analysis, which was used to evaluate the apparent activation energy corresponding to the single combustions and to the co-combustion of blends. Highlights: Primary (L1) and secondary (L2) pulp mill sludge showed different combustion behaviour. DTG and DSC combustion curves of L1, L2 and a bituminous coal largely diverged. The co-combustion of coal with pulp mill sludge (10 wt.%) resembled that of coal. Estimated activation energy for blends combustion was slightly higher than for coal.